Inventarisasi Penyakit di Kebun Salak Pondoh (Salacca Zalacca Var Pondoh) di Desa Rumah Lengo Kecamatan STM Hulu Kabupaten Deli Serdang Sumatera Utara - Ameliya, Ameliya; Azwana, Azwana (Universitas Medan Area, 2024)
Salak pondoh (Salacca zalacca var pondoh) is a plant native to Indonesia and this fruit has quite high value and is liked by many consumers in Indonesia. However, the quality of snake fruit can decrease due to damage caused by plant pathogens such as fungi (fungi). This of course can result in snake fruit being unfit for consumption because it is damaged. The results of the research found that there are three types of diseases that attack Pondoh salak plants which are caused by fungi, namely brown leaf spot disease caused by the fungus Pestalotia sp. with an attack intensity of 42%-54%, stem rot disease caused by the fungus Corticium salmonicolor with an attack intensity of 26%-30%, and fruit rot disease caused by the fungus Chalaropsis sp. with an attack intensity of 20% -23%. The cause of fungal disease attacks on Pondoh salak plants is also triggered by the humid environmental conditions around the Pondoh salak plantations and the rainy season, making it easier for the fungus to reproduce.